Preservation effect of cinnamon and clove essential oil vapors on shelled walnut - Berta, Máté; Molnár, István; Zentai, Ádám; Kecskeméti, Anita; Kerekes, Erika Beáta; Nacsa-Farkas, Elvira; Gömöri, Csilla; Vidács, Anita; Kocsubé, Sándor; Bencsik, Ottó; Szekeres, András; Vágvölgyi, Csaba; et al. (Acta Biologica Szegediensis, 2019)
Shelled walnut (Juglans regia) kernels are prone to rancidity during storage. In this study we examined the preservation effect of cinnamon and clove essential oil (EO) vapors compared to cold storage and vacuum packaging by measuring the hexanal content, indicating rancidity, in stored walnut kernels. Odor and taste of stored shelled walnut was investigated by sensory evaluation and by measuring residues of the main EO components in the kernels. During storage under EO vapors, cinnamaldehyde and eugenol were absorbed on the surface of walnuts in a time-dependent manner changing the odor and taste of the kernels. Clove (Syzygium aromaticum) EO prevented rancidity and EO treated kernels were rated as acceptable by the sensory panel while cinnamon EO treatment increased rancidity compared to the other treatments and the control samples.